Experience with 122 consecutive liver transplant procedures at King Faisal Specialist Hospital and Research Center - Al-Sebayel, Mohammed (Ann Saudi Med, 2007)
BACKGROUND: Saudi Arabia is a leading country in the Middle East in the field of deceased-donor liver transplantation (DDLT) and living-donor liver transplantation (LDLT). We present out experience with DDLT and LDLT at King Faisal Specialist Hospital and Research Center (KFSHRC) for the period from April 2001 to January 2007. PATIENTS AND METHODS: We performed 122 LT procedures (77 DDLTs and 45 LDLTs) in 118 patients (4 retransplants) during this period of time. RESULTS: The number of adult and pediatric procedures was 107 and 11, respectively. The overall male/female ratio was 66/52 and the median age of patients was 43 years (range, 2–63 years). In the DDLT group, the median operating time was 8 hours (range, 4–19), the median blood transfusion was 6 units (range, 0–40), and the median hospital stay was 13 days (range, 6–183). In the DDLT group, after a mean follow-up period of 760 days (range, 2–2085), the overall patient and graft survival rate was 86%. In the LDLT group, the median operating time was 11 hours (range, 7–17), the median blood transfusion was 4 units (range, 0–65), and the median hospital stay was 15 days (range, 7–127). In the LDLT group, and after a mean follow-up period of 685 days (range, 26–1540), the overall patient and graft survival rates were 90% and 80%, respectively with no significant difference in patient and graft survivals between groups. Biliary complications were significantly higher in LDLT compared to DDLT (P<0.05). Vascular complications were also significantly higher in LDLT compared DDLT (P<0.05). CONCLUSIONS: Both DDLT and LDLT are being successfully performed at KFSHRC with early experience indicating a higher rate of biliary and vascular complications in the LDLT group.